Discriminating the Short-Term Action of Root and Foliar Application of Humic Acids on Plant Growth: Emerging Role of Jasmonic Acid - De Hita, David; Fuentes, Marta; Fernández, Victoria; Zamarreño, Angel M.; Olaetxea, Maite; García-Mina, Jose M. (Frontiers in Plant Science, 2020)
Humic substances (HS, fulvic and humic acids) are widely used as fertilizers or plant growth stimulants, although their mechanism of action still remains partially unknown. Humic substances may be applied either directly to the soil or as foliar sprays. Despite both kind of applications are commonly used in agricultural practices, the major part of the studies regarding the elicited response in plants as a consequence of the treatment with HS are based on the root-application of these substances. The present work aimed at discriminating between the mechanisms of action of foliar application versus root application of a sedimentary humic acid (SHA) on plant development. For this purpose, six markers related to plant phenotype, plant morphology, hormonal balance and root-plasma membrane H+-ATPase were selected. Both application strategies improved the shoot and root growth. Foliar applied- and root applied-SHA shared the capacity to increase the concentration of indole-3-acetic acid in roots and cytokinins in leaves. However, foliar application did not lead to short-term increases in either abscisic acid root-concentration or root-plasma membrane H+-ATPase activity which are, however, two crucial effects triggered by SHA root-application. Both application modes increased the root concentrations of jasmonic acid and jasmonoyl-isoleucine. These hormonal changes caused by foliar application could be a stress-related symptom and connected to the loss of leaves trichromes and the diminution of chloroplasts size seen by microscopy. These results support the hypothesis that the beneficial effects of SHA applied to roots or leaves may result from plant adaptation to a mild transient stress caused by SHA application.